Project-Based Learning Approach in Autonomous Vehicle Course During Pandemic Outbreak: A Study Case - Saputro, Joko Slamet; Adriyanto, Feri; Anwar, Miftahul; Ibrahim, Sutrisno; Latifan, Syaifullah Filard (Journal of Education Technology, 2024)
The COVID-19 pandemic has had a major impact on the education sector, including universities, which must immediately switch from classical learning to online learning. In the Electrical Engineering study program at Sebelas Maret University, one of the main challenges is achieving the learning output targets set in the courses, especially in the Autonomous Vehicles course. This study aims to examine the implementation of the Project-Based Learning (PBL) approach in the Autonomous Vehicles course during the pandemic, as well as to understand students' perceptions of the learning methods applied, including through online learning with blended learning. The study used a case study approach, where students were divided into three groups to work on an autonomous vehicle simulation project using Webots software. Each group faced different challenges, such as avoiding obstacles, overtaking other vehicles, and self-parking. A questionnaire was used to collect data on students' perceptions of the implementation of PBL. The results showed that PBL was successfully implemented well in the Autonomous Vehicles course, although there were several challenges, especially related to the duration of the project. Overall, students felt that this method was effective in improving their technical and soft skills, such as critical thinking, problem solving, and teamwork.